Mechanisms contributing to differential regulation of PAX3 downstream target genes in normal human epidermal melanocytes versus melanoma cells. - Danielle Bartlett; Glen M Boyle; Mel Ziman; Sandra Medic (PLoS ONE, 2015)
Melanoma is a highly aggressive and drug resistant form of skin cancer. It arises from melanocytes, the pigment producing cells of the skin. The formation of these melanocytes is driven by the transcription factor PAX3 early during embryonic development. As a result of alternative splicing, the PAX3 gene gives rise to eight different transcripts which encode isoforms that have different structures and activate different downstream target genes involved in pathways of cell proliferation, migration, differentiation and survival. Furthermore, post-translational modifications have also been shown to alter the functions of PAX3. We previously identified PAX3 downstream target genes in melanocytes and melanoma cells. Here we assessed the effects of PAX3 down-regulation on this panel of target genes in primary melanocytes versus melanoma cells. We show that PAX3 differentially regulates various downstream target genes involved in cell proliferation in melanoma cells compared to melanocytes. To determine mechanisms behind this differential downstream target gene regulation, we performed immunoprecipitation to assess post-translational modifications of the PAX3 protein as well as RNAseq to determine PAX3 transcript expression profiles in melanocytes compared to melanoma cells. Although PAX3 was found to be post-translationally modified, there was no qualitative difference in phosphorylation and ubiquitination between melanocytes and melanoma cells, while acetylation of PAX3 was reduced in melanoma cells. Additionally, there were differences in PAX3 transcript expression profiles between melanocytes and melanoma cells. In particular the PAX3E transcript, responsible for reducing melanocyte proliferation and increasing apoptosis, was found to be down-regulated in melanoma cells compared to melanocytes. These results suggest that alternate transcript expression profiles activate different downstream target genes leading to the melanoma phenotype.